Cefepime: a novel cause of thrombocytopaenia. Issue 1 (17th January 2022) - Muhammad, Shoaib; Ahmad, Soban; Khan, Behram Ahmed; Yousaf, Amman
Abstract : Thrombocytopaenia is a commonly encountered finding in hospitalised patients. Many antibiotics, especially beta-lactams, are well known to cause thrombocytopaenia by an immune-mediated mechanism. We present a 55-year-old woman who was admitted to the hospital with a complicated urinary tract infection resulting in right-sided pyonephrosis and pararenal abscess. She was observed to develop thrombocytopaenia after initiation of cefepime therapy. Following an extensive work-up for her new-onset thrombocytopaenia, she was diagnosed as a case of a drug (cefepime)-induced thrombocytopaenia. Her platelet count recovered back to normal levels after cessation of cefepime therapy. Based on our PubMed search, there are only a few cases of cefepime-induced thrombocytopaenia published in the literature. This paper illustrates that physicians should include cefepime among the possible aetiologies of thrombocytopaenia. Additionally, this article outlines the currently available approaches to the diagnosis and management of drug-induced thrombocytopaenia.